The future of neuroprotection in stroke. Issue 2 (4th November 2020) - Chamorro, Ángel; Lo, Eng H; Renú, Arturo; van Leyen, Klaus; Lyden, Patrick D
Abstract : Investigators acknowledge the limitations of rodent or non-human primate stroke models, hundreds of putative neuroprotectants have been evaluated in preclinical models, but not one has entered the clinical realm. Initial studies focused on the neuron, but in recent years the focus has widened to also include other neural cells including astrocytes, pericytes and endothelial cells, which together form the neurovascular unit. Some new developments raise renewed hope for neuroprotection: the appearance of new compounds with multiple mechanisms of action, or the promulgation of new standards for a rigorous preclinical testing. At the bedside in the last 5 years, uric acid and nerinetide are the only compounds tested for clinical efficacy in randomised controlled trials (RCTs), where all patients had to receive reperfusion therapies, either intravenous thrombolysis and/or mechanical thrombectomy. In addition, otaplimastat, 3K3A-activated protein C (APC), intra-arterial verapamil and intra-arterial hypothermia were also assessed in combination with reperfusion therapy, but in RCTs that only included feasibility or safety outcomes. Some of these compounds yielded promising results which are discussed in this review. Altogether, a deeper knowledge of the mechanisms involved in the ischaemic death process at the neurovascular unit, an improved preselection and evaluation of drugs at the preclinical stage and the testing of putative neuroprotectants in enriched clinical studies of patients receiving reperfusion therapies, might prove more effective than in the past to reverse a dismal situation that has lasted already too long.